Green energy generator / Naqiuddin Ajmain Yusdi Nasir & Muhammad Ikram Ahmad Zaidi - Yusdi Nasir, Naqiuddin Ajmain; Ahmad Zaidi, Muhammad Ikram (2015)
All of us must have at least one mobile phone. In modem world, people normally have two smartphone to deal contact with work and others. The problem is, battery of smartphone will drop faster if we frequently use it in certain time. So this project is about portable green energy charger which can least their fear about percent of battery left. The idea came from power bank which commonly used by people nowadays to constant their battery of smartphone. But, the problem is power bank have limit power to be distribute to the smartphone (i.e. 20000mAh). So, the green charger generator will solved all sorts of consequential problems. Benefit of the device is it does not need to recharge itself because it can generate energy by itself. It is not depend on any electrical source to distribute power to smartphone. The device also can support until 12 volts where user can choose either want to 5 volts, 9 volts or 12 volts. A LCD will display the voltage chose by user